Liquid gold: assessing groundwater quality at the historic Kolar gold fields, Karnataka, India - Paulose, Jojo; Xavier, Jobi (Brawijaya University, 2025)
To access the ecological sustainability and resilience, it is necessary to periodically examine various ecological properties in areas with high pollution and contaminant risks. Kolar Gold Fields (KGF) in Kolar, Karnataka, showcases one amongst the India's most contaminated zones because of the extensive gold mining and their lingering effects. In KGF, quality of ground water has severely reduced as there exist extensive mining tailings, locally referred as cyanide dumps, which have been neglected for several preceding years without proper disposal strategies. The current approach focuses on the water pollution caused by heavy metal deposits in the KGF region. Groundwater samples were sampled from Oorgam, an abandoned region in KGF, and subsequently filtered for water quality examinations. The investigation documented concentrations of several metals, including cadmium (0.068 ± 0.0024 ppm), lead (0.288 ± 0.0016 ppm), nickel (0.058 ± 0.0047 ppm), and chromium (0.23 ± 0.0235 ppm) and have met the standard specifications in accordance with World Health Organization (WHO). Prominent pH disparity was documented amongst the experimental samples, with a detectable pH drop in the aqua-purified water on comparison to the positive control. The test results imply that the water samples collected from KGF remains unpotable for consumption or irrigation due the persistence of high levels of heavy metals concentration. This study underscores the urgent requisite for remedial approach to ensure water safety for drinking and irrigation in the area.